PHARMACOLOGICAL POTENTIALS OF PYRIMIDINE DERIVATIVE: A REVIEW - Dansena, Harshalata; HJ, DHONGADE; Chandrakar, Kavita (Asian Journal of Pharmaceutical and Clinical Research, 2015)
The chemistry of pyrimidine derivatives plays an important role in the field of drugs, agriculture chemicals and many biological processes. The chemistry of pyrimidine is a provoking field. In recent decades, a large number of pharmacological studies has been done on pyrimidine & there derivative. But still more research is required in order to necessity the biological compounds. Â Numerous methods for the synthesis of pyrimidine and also their diverse reaction generate an enormous scope in the field of medicinal chemistry. The utility of pyrimidines as synthon for various biologically active compounds has given impetus to these studies. Â The pyrimidine derivatives show various biological activities including antitubercular, antioxidant, anti-inflammatory, anticonvulsant, antimicrobial, antibacterial, antiplasmodial, antifungal, anticancer, and analgesic activity. This article aims to review the recent works on pyrimidine derivatives together with the biological potential during the past years. Keywords: Pyrimidine, Pharmacological studies, Anticancer, Antitubercular